2007
DOI: 10.1158/1535-7163.mct-06-0303
|View full text |Cite
|
Sign up to set email alerts
|

The role of spermidine/spermineN1-acetyltransferase in determining response to chemotherapeutic agents in colorectal cancer cells

Abstract: Polyamines have been shown to play a role in the growth and survival of several solid tumors, including colorectal cancer. We identified the polyamine catabolic enzyme spermidine/spermine N 1 -acetyltransferase (SSAT) as being one of the most highly inducible genes in two DNA microarray screens to identify novel determinants of response to chemotherapeutic agents in colorectal cancer. SSAT was shown to be inducible in response to 5-fluorouracil (5-FU) or oxaliplatin in parental and drugresistant HCT116 cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 37 publications
1
39
1
Order By: Relevance
“…In particular, we observed a concordant modulation at every time point of SAT-1 and SRM, both involved in the cellular polyamine metabolism [37]. The concerted up and downregulation of the catabolic SAT-1 and the biosynthetic SRM enzyme, respectively, is expected to result in a reduction of the cellular polyamine pools, a condition associated with growth inhibition and apoptosis [38]. Indeed, targeting the polyamine pathway may have clinical relevance in anticancer therapy 3 .…”
Section: Discussionmentioning
confidence: 97%
“…In particular, we observed a concordant modulation at every time point of SAT-1 and SRM, both involved in the cellular polyamine metabolism [37]. The concerted up and downregulation of the catabolic SAT-1 and the biosynthetic SRM enzyme, respectively, is expected to result in a reduction of the cellular polyamine pools, a condition associated with growth inhibition and apoptosis [38]. Indeed, targeting the polyamine pathway may have clinical relevance in anticancer therapy 3 .…”
Section: Discussionmentioning
confidence: 97%
“…DENSPM up-regulates SSAT and down-regulates the biosynthetic pathway enzymes ODC and SAMDC causing depletion of polyamine pools and this analog has been tested in Phase I and Phase II clinical trials (13)(14)(15)(16) and had no demonstrable single agent activity. Our studies and others have shown that when platinum drugs are combined with DENSPM, the synergistic SSAT activity and polyamine pool depletion that occurs in tumor cells is significantly greater than that by either of the single agents (7,17,18). The biogenic polyamine spermine is able to form chelates with several metal ions providing flexible linkers and conferring hydrophobic character to the molecule, which is important for drug uptake and enables a distinct interaction with DNA when compared to cisplatin.…”
Section: Introductionmentioning
confidence: 68%
“…A significant body of studies accumulated in the last several years indicate that platinum drugs have an effect on the polyamine pathway (6,7,17,18,35,36). Our own Affymetrix experiments with oxaliplatin and cisplatin indicate that both of these drugs up-regulated the polyamine catabolic pathway enzymes SSAT and SMO and down-regulated the biosynthetic pathway enzymes SAMDC and ODC (6).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations